The Effect of Nanohydrogel Oral Insulin Therapy on Serum Glucose and Insulin Level in Patients with Type 2 Diabetes: A Pilot Study - Vali Ahmadi, Jalil Karnoosh-Yamchi, Akbar Aliasgharzadeh, Alireza (Tabriz University of Medical Sciences, 2016)
Background: This pilot study was designed to investigate the effect of orally delivered nanohydrogel insulin on serum glucose and insulin levels in patients with type 2 diabetes (T2DM). Methods: In this pilot before-after study, 8 T2DM patients received 300 IU insulin loaded nanohydrogel orally and the serum concentration of glucose and insulin were measured before treatment and consecutively during treatment. The area under the curve (AUC) was calculated for serum glucose and insulin and repeated measures of ANOVA, paired t-test were used for statistical analysis. Results: The changes in serum glucose level was not significant pretreatment (p=0.10) and during oral insulin treatment (p=0.71). Compared with pretreatment value, the serum glucose level was significantly lower in 7 A.M. (immediately after insulin therapy) and 8.30 A.M. during oral insulin treatment. The maximum reduction was observed 1.5 hours after insulin therapy and its effect lasted for more than 6 hours. The mean AUC of glucose was insignificantly decreased (p=0.16). The pretreatment (p=0.10) and during treatment (p=0.30) changes in serum insulin level were not statistically significant. The serum insulin level was increased significantly immediately after oral insulin therapy compared with pretreatment values. The mean AUC of insulin increased marginally significant (p=0.056). Conclusion: The results of the present pilot study showed that 300IU nanohydrogel oral insulin was effective in rapid lowering of serum glucose and its glucose lowering effect lasting for more than 6 hours. However, for any precise conclusions further studies with longer duration are needed.